2015
DOI: 10.1016/j.pharep.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HMG-CoA reductase inhibitors on the pharmacokinetics of nifedipine in rats: Possible role of P-gp and CYP3A4 inhibition by HMG-CoA reductase inhibitors

Abstract: The increased bioavailability of nifedipine may be mainly due to inhibition of both P-gp in the small intestine and CYP3A subfamily-mediated metabolism of nifedipine in the small intestine and/or in the liver and to the reduction of the CL/F of nifedipine by fluvastatin and simvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(55 reference statements)
2
11
1
Order By: Relevance
“…Recently, an in vitro study has shown that simvastatin inhibited CYP3A4/5 and P-gp activity (Lee et al, 2015). An in vivo animal study performed by the same authors showed that concomitant administration of simvastatin with nifedipine, a CYP3A/5 and P-gp substrate, significantly increased the absolute bioavailability of nifedipine by 150% (Lee et al, 2015). On the other hand, atorvastatin inhibited CYP3A/5 but not P-gp activity in vitro , and had no impact on nifedipine pharmacokinetics in vivo (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an in vitro study has shown that simvastatin inhibited CYP3A4/5 and P-gp activity (Lee et al, 2015). An in vivo animal study performed by the same authors showed that concomitant administration of simvastatin with nifedipine, a CYP3A/5 and P-gp substrate, significantly increased the absolute bioavailability of nifedipine by 150% (Lee et al, 2015). On the other hand, atorvastatin inhibited CYP3A/5 but not P-gp activity in vitro , and had no impact on nifedipine pharmacokinetics in vivo (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo animal study performed by the same authors showed that concomitant administration of simvastatin with nifedipine, a CYP3A/5 and P-gp substrate, significantly increased the absolute bioavailability of nifedipine by 150% (Lee et al, 2015). On the other hand, atorvastatin inhibited CYP3A/5 but not P-gp activity in vitro , and had no impact on nifedipine pharmacokinetics in vivo (Lee et al, 2015). According to the FDA classification 1 , simvastatin would therefore be considered as a weak CYP3A/5 inhibitor (≥1.25 but <2-fold increase in AUC).…”
Section: Discussionmentioning
confidence: 99%
“…As AC is a substrate of CYP3A4 enzymes, which is predominantly metabolized by CYP3A4 (Lee et al. 2015 ), and therefore, we infer that the herb-drug interaction between AC and DST may occur due to the effects of salvianolic acid B on the activity of CYP3A4.…”
Section: Resultsmentioning
confidence: 82%
“…As ALDP is a substrate of CYP3A4 enzymes, which is predominantly metabolized by CYP3A4 (Lee et al. 2015), and therefore, we infer that the herb–drug interaction between ALDP and DST may occur due to the effects of salvianolic acid B on the activity of CYP3A4.…”
Section: Resultsmentioning
confidence: 83%